Human planet [videorecording (DVD)] : the complete series - Hurt, John, 1940-2017 (BBC Earth ; Distributed by Warner Home Video, 2011)
Following in the footsteps of Planet Earth and Life, this epic eight-part blockbuster is a breathtaking celebration of the amazing, complex, profound, and sometimes challenging relationship between humankind and nature. Humans are the ultimate animals - the most successful species on the planet. Each episode focuses on a particular habitat and reveals how its people have created astonishing solutions in the face of extreme adversity.